Switching from insulin to oral sulfonylureas in patients with diabetes due to Kir6.2 mutations. - Pearson, E; Flechtner, I; Njølstad, P; Malecki, M; Flanagan, SE; Larkin, B; Ashcroft, F; Klimes, I; Codner, E; Iotova, V; Slingerland, A; Shield, J; et al. (2006)
BACKGROUND: Heterozygous activating mutations in KCNJ11, encoding the Kir6.2 subunit of the ATP-sensitive potassium (K(ATP)) channel, cause 30 to 58 percent of cases of diabetes diagnosed in patients under six months of age. Patients present with ketoacidosis or severe hyperglycemia and are treated with insulin. Diabetes results from impaired insulin secretion caused by a failure of the beta-cell K(ATP) channel to close in response to increased intracellular ATP. Sulfonylureas close the K(ATP) channel by an ATP-independent route. METHODS: We assessed glycemic control in 49 consecutive patients with Kir6.2 mutations who received appropriate doses of sulfonylureas and, in smaller subgroups, investigated the insulin secretory responses to intravenous and oral glucose, a mixed meal, and glucagon. The response of mutant K(ATP) channels to the sulfonylurea tolbutamide was assayed in xenopus oocytes. RESULTS: A total of 44 patients (90 percent) successfully discontinued insulin after receiving sulfonylureas. The extent of the tolbutamide blockade of K(ATP) channels in vitro reflected the response seen in patients. Glycated hemoglobin levels improved in all patients who switched to sulfonylurea therapy (from 8.1 percent before treatment to 6.4 percent after 12 weeks of treatment, P<0.001). Improved glycemic control was sustained at one year. Sulfonylurea treatment increased insulin secretion, which was more highly stimulated by oral glucose or a mixed meal than by intravenous glucose. Exogenous glucagon increased insulin secretion only in the presence of sulfonylureas. CONCLUSIONS: Sulfonylurea therapy is safe in the short term for patients with diabetes caused by KCNJ11 mutations and is probably more effective than insulin therapy. This pharmacogenetic response to sulfonylureas may result from the closing of mutant K(ATP) channels, thereby increasing insulin secretion in response to incretins and glucose metabolism. (ClinicalTrials.gov number, NCT00334711 [ClinicalTrials.gov].).